THE ROLE OF INSTITUTIONAL COOPERATION IN ENSURING HUMAN INTERESTS IN THE CONTEXT OF NEW UZBEKISTAN. (Scientific journal of the Fergana State University, 2026)
This article analyzes the role and significance of institutional cooperation in ensuring human interests in the context of New Uzbekistan. It explores the interaction between state institutions, civil society organizations, non-governmental structures, and international institutions in protecting human rights and freedoms, promoting social justice, and improving citizens’ welfare.